2021
DOI: 10.21203/rs.3.rs-366984/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Financial Protection of National Health Insurance: Evidence From a Cross Section of State and Federal Workers in Akwa Ibom, Nigeria 

Abstract: Background: Public health insurance schemes can offer households financial protection against health care costs and help to resolve inequality in health care provision. The current study evaluates the impact of the Nigerian National Health Insurance Scheme (NHIS) in reducing financial hardship for a sample of Nigerian households working in the health and higher education sectors. The data allows us to examine the variation in the financial protection effects across different income groups and explore differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…The included studies reported different effects of NHI on CHE at different thresholds of household total income (expenditure) and non-food expenditure. In more than half of the included studies (5 out of 9), NHI was reported to have a positive effect (protective factor) on CHE [3942, 46]. In addition, one of these five studies reported a positive effect of NHI on impoverishment due to health spending [40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies reported different effects of NHI on CHE at different thresholds of household total income (expenditure) and non-food expenditure. In more than half of the included studies (5 out of 9), NHI was reported to have a positive effect (protective factor) on CHE [3942, 46]. In addition, one of these five studies reported a positive effect of NHI on impoverishment due to health spending [40].…”
Section: Resultsmentioning
confidence: 99%
“…This study focused on FSSHIP and as such described its financing mechanism [39]. It reported that the funding for the FSSHIP comes from an annual premium that is 15% of an employee’s annual basic salary which is a shared contribution between the employee (5%) and the employer (10%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations